Coverslips
By improving the fracture toughness of the cover glass and forming a compressive stress layer, the problem of the cover glass in the prior art is easily broken when used in outdoor, and achieving higher scratch resistance and mechanical strength.
Patent Information
- Application Number
- JP2023102884
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-12-26
- Filing Date
- 2023-06-23
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2038-12-21
AI Technical Summary
The covered glass of existing touch panel displays is susceptible to hard scratches when used outdoors, causing glass to break, and increasing the hardness of the glass will affect its fluidity and moldability.
The scratch resistance of the glass is improved by increasing the fracture toughness of the cover glass to 0.9MPa·m0.5 or higher, combined with a specific glass composition and a surface compressive stress layer.
It improves the scratch resistance of the covered glass, reduces the width and depth of scratches, and effectively prevents glass from rupturing even when subjected to hard scratches.
Smart Images

Figure 0007663107000003 
Figure 0007663107000004 
Figure 0007663107000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a cover glass, and more particularly to a cover glass suitable for touch panel displays of mobile phones, digital cameras, PDAs (personal digital assistants) and the like. [Background technology]
[0002] Mobile phones, digital cameras, PDAs (personal digital assistants), etc. are becoming more and more popular. For these applications, ion-exchanged tempered glass is used as the cover glass for touch panel displays (see Patent Document 1 and Non-Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-83045 A [Patent Document 2] Special Publication No. 2016-524581 [Non-patent literature]
[0004] [Non-Patent Document 1] Tetsuro Izumiya et al., "New Glass and its Physical Properties", First Edition, Management Systems Research Institute, August 20, 1984, pp. 451-498 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0005] Cover glass, especially that used for smartphones, is often used outdoors and is prone to hard scratches, i.e. scratches with large width and depth. As a result, the cover glass is prone to breakage from the scratches. Therefore, it is important to improve the scratch resistance of the cover glass.
[0006] Increasing the hardness of the cover glass has been considered as a method for improving scratch resistance. More specifically, conventional glass has a much lower hardness than silica (sand), which is abundant on the ground, and therefore has the property of being easily scratched due to silica. It is therefore thought that increasing the hardness of the cover glass would make the surface less susceptible to scratches. However, when an attempt is made to increase the hardness of the cover glass, the high-temperature viscosity of the glass increases, significantly reducing its melting property and formability. Furthermore, the balance of the glass composition is lost, making it more likely that devitrified particles will occur during forming. As a result, it becomes difficult to obtain a good product.
[0007] It is also known that forming a hard thin film on the glass surface increases the hardness of the cover glass (see, for example, Patent Document 2). However, forming a hard thin film on the glass surface may reduce the transparency of the cover glass or cause warping of the cover glass due to film stress.
[0008] Although sapphire appears to be suitable for the cover member due to its high hardness, it is difficult to mass-produce large sapphire plate-shaped bodies.
[0009] The present invention has been made in view of the above circumstances, and its technical object is to invent a cover glass that is highly scratch-resistant. [Means for solving the problem]
[0010] As a result of various investigations conducted by the present inventors, it was found that the fracture toughness of glass, K 1C It was found that the size of the crack is closely related to the fracture toughness K 1C The inventors have found that the above technical problems can be solved by increasing the fracture toughness K 1C is 0.9MPa m 0.5 The fracture toughness K 1C" was measured using the Single-Edge-Precracked-Beam method (SEPB method) based on JIS R1607 "Fracture toughness test method for fine ceramics". The SEPB method measures the maximum load until the test piece breaks in a three-point bending test of a precracked test piece, and calculates the plane strain fracture toughness K from the maximum load, precrack length, test piece dimensions, and bending support distance. 1C This is a method to determine the fracture toughness K 1C The measured value is the average of five measurements.
[0011] As described above, the cover glass of the present invention has a fracture toughness K 1C The fracture toughness K is 0.9 or more. This makes it difficult for the surface to be scratched, and even if hard scratches are made, the width and depth of the scratches can be reduced. 1C FIG. 2 is a graph showing the relationship between fracture toughness K 1C As is clear from Figures 1 and 2, the fracture toughness is 0.9 MPa m 0.5 It can be seen that at larger values, the width and depth of the scratches are significantly reduced.
[0012] In addition, the cover glass of the present invention preferably has an MgO content in the glass composition of more than 10 mol %.
[0013] The cover glass of the present invention preferably contains, in mole percent, 30-70% SiO2, 5-30% Al2O3, 0-15% B2O3, 0-7% Li2O, 0-20% Na2O, 0-10% K2O, and more than 10-50% MgO as a glass composition.
[0014] Moreover, the cover glass of the present invention preferably has a P2O5 content of 1 mol % or more in the glass composition.
[0015] Moreover, the cover glass of the present invention preferably satisfies the relationship [MgO] / [Al2O3] ≥ 1.0, where "[MgO] / [Al2O3]" refers to the molar percentage content of MgO divided by the molar percentage content of Al2O3.
[0016] Moreover, the cover glass of the present invention preferably satisfies the relationship [MgO] / [Na2O] ≥ 1.0, where "[MgO] / [Na2O]" refers to the molar percentage content of MgO divided by the molar percentage content of Na2O.
[0017] Moreover, in the cover glass of the present invention, the content of Li2O in the glass composition is preferably more than 0.1 mol %.
[0018] The cover glass of the present invention preferably contains, in mole percent, 60-80% SiO2, 1-30% Al2O3, 0-15% B2O3, more than 0.1-30% Li2O, 0-20% Na2O, 0-10% K2O, and 0-20% MgO as a glass composition.
[0019] Moreover, the cover glass of the present invention preferably contains 0.1 mol % or more of Y2O3 in the glass composition.
[0020] The cover glass of the present invention preferably has a Young's modulus of at least 90 GPa. Here, the "Young's modulus" can be measured by a well-known resonance method.
[0021] The cover glass of the present invention preferably has a compressive stress layer formed by ion exchange on the surface.
[0022] In addition, the cover glass of the present invention preferably has a compressive stress layer having a compressive stress value of 300 MPa or more and a stress depth of 15 μm or more. Here, the "compressive stress value" and "stress depth" refer to values calculated using a surface stress meter (Orihara Seisakusho's surface stress meter FSM-6000LE).
[0023] The cover glass of the present invention preferably has a CT limit of more than 65 MPa. Here, the "CT limit" refers to the number of fragments with dimensions of 0.1 mm or more that is 100 pieces / inch. 2 This refers to the internal tensile stress value at which the number of fragments is 100 per inch. 2 The "internal tensile stress value that will cause delayed fracture" is determined by first performing an indenter test using a diamond tip on a surface plate, and determining the number of fragments at which delayed fracture occurs at 100 pieces per inch. 2 The number of fragments at CTcv values (2 points) exceeding 100 fragments / inch 2 The number of fragments data at CTcv values (2 points) when the number of fragments is less than 100 is collected, and then an exponential approximation curve is drawn from the number of fragments data at a total of 4 CTcv values, and the CTcv value at which the number of fragments becomes 100 is calculated as the CT limit from the approximation curve. The CTcv value can be obtained using the FsmV software of Orihara Seisakusho's surface stress meter FSM-6000LE. The number of fragments data at each point is the average value of three measurements.
[0024] The cover glass of the present invention is preferably used for a touch panel display. [Brief description of the drawings]
[0025] [Figure 1] 1 is a graph showing the relationship between fracture toughness K1C and crack width. [Diagram 2] 1 is a graph showing the relationship between fracture toughness K1C and crack depth. [Diagram 3] 1 is a graph showing the relationship between the plate thickness and the CT limit of the sample in the column [Example 2]. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] In the cover glass of the present invention, the fracture toughness K 1C is 0.9MPa m 0.5 or more, preferably 1.0 MPa m 0.5 More preferably, it is 1.1 to 3.5 MPa m0.5 In particular, the fracture toughness K 1C is 0.9MPa m 0.5 It is preferable that the viscosity is equal to or higher than 1.0 MPa m, and more preferable that the viscosity is equal to or higher than 1.0 MPa m 0.5 More preferably, it is 1.1 to 3.5 MPa m 0.5 Fracture toughness K 1C If the CT limit is too small, the surface of the cover glass is easily scratched. Even if a hard scratch occurs, the width and depth of the scratch tend to be large. Furthermore, after ion exchange treatment, the non-brittleness (CT limit) becomes high.
[0027] The cover glass of the present invention preferably has a Young's modulus of 90 GPa or more, 100 GPa or more, particularly 105 to 150 GPa. If the Young's modulus is low, the cover glass will be easily bent when the plate thickness is thin.
[0028] The cover glass of the present invention preferably has a glass composition falling within glass composition range A and / or glass composition range B shown below.
[0029] Glass composition range A contains, in mole percent, SiO2 30-70%, Al2O3 5-30%, B2O3 0-15%, Li2O 0-7%, Na2O 0-20%, K2O 0-10%, and MgO 10% to 50%. The reasons for limiting the content range of each component are as follows. In the explanation of the content range of each component, % indicates mole percent unless otherwise specified.
[0030] SiO2 is a component that forms a glass network. The content of SiO2 is preferably 30 to 70%, 32 to 61%, 33 to 55%, or less than 34 to 50%, particularly 35 to 45%. If the content of SiO2 is too low, vitrification becomes difficult, and the thermal expansion coefficient becomes too high, so that the thermal shock resistance is likely to decrease. On the other hand, if the content of SiO2 is too high, meltability and moldability tend to decrease, and the thermal expansion coefficient becomes too low, so that it is difficult to match the thermal expansion coefficient of the surrounding materials.
[0031] Al2O3 has high fracture toughness K 1C It is an ingredient that increases the fracture toughness K, and also increases the ion exchange performance, strain point, and Young's modulus. If the Al2O3 content is too low, 1C The ion exchange performance is likely to be reduced, and there is a risk that the ion exchange performance cannot be fully exhibited. Therefore, the content of Al2O3 is preferably 5% or more, 8% or more, 10% or more, 12% or more, 14% or more, and particularly 15% or more. On the other hand, if the content of Al2O3 is too high, the high-temperature viscosity increases, and the melting property and moldability are likely to be reduced. In addition, devitrification crystals are likely to precipitate in the glass, making it difficult to form into a plate shape by the overflow downdraw method or the like. In particular, when an alumina-based refractory is used as the molded body refractory and the glass is formed into a plate shape by the overflow downdraw method, devitrification crystals of spinel are likely to precipitate at the interface with the alumina-based refractory. Furthermore, the acid resistance is also reduced, making it difficult to apply to the acid treatment process. Therefore, the content of Al2O3 is preferably 30% or less, 25% or less, and particularly 21% or less.
[0032] B2O3 is a component that reduces the high-temperature viscosity and density, stabilizes the glass, and lowers the liquidus temperature. However, if the content of B2O3 is too high, the Young's modulus is likely to decrease. Therefore, the content of B2O3 is preferably 0 to 15%, 0.1 to 10%, 1 to 7%, and particularly preferably 2 to 5%.
[0033] Li2O is an ion exchange component, and also a component that reduces high-temperature viscosity and improves meltability and formability, as well as fracture toughness K 1C It is a component that significantly increases the content of Li2O. On the other hand, if the content of Li2O is too high, the devitrification resistance is likely to decrease, and there is a risk that the Li2O will dissolve into the ion exchange solution during ion exchange treatment, deteriorating the ion exchange solution. Therefore, the content of Li2O is preferably 0 to 7%, 0 to 3%, 0 to 1.5%, 0 to less than 1%, 0 to 0.5%, 0 to 0.3%, 0 to less than 0.1%, and particularly preferably 0.01 to 0.05%.
[0034] Na2O is an ion exchange component, which increases the compressive stress value of the compressive stress layer, and also reduces the high-temperature viscosity to increase the melting property and formability. Na2O also increases the resistance to devitrification, and in particular suppresses the devitrification caused by the reaction with an alumina-based refractory. If the Na2O content is too high, it becomes difficult to obtain the above effects. On the other hand, if the Na2O content is too low, the high-temperature viscosity increases, which decreases the melting property and formability, and the compressive stress value of the compressive stress layer is likely to decrease. Therefore, the Na2O content is preferably 0 to 20%, 1 to 17%, and particularly 5 to 15%.
[0035] K2O is a component that reduces high-temperature viscosity and improves melting and moldability, but among alkali metal oxides, it is a component that reduces the compressive stress value of the compressive stress layer and increases the stress depth, so it is not advantageous from the viewpoint of increasing the compressive stress value. Therefore, the content of K2O is preferably 0 to 10%, 0 to 5%, and particularly 0 to less than 1%.
[0036] MgO has high fracture toughness. 1C It is a component that significantly increases the melting property and formability, and is a component that increases the melting property and formability. However, if the content of MgO is too high, the devitrification resistance is likely to decrease, and in particular, it becomes difficult to suppress the devitrification caused by the reaction with the alumina-based refractory. Therefore, the content of MgO is preferably more than 10 to 50%, 15 to 45%, 20 to 42%, 25 to 40%, and particularly 30 to 35%.
[0037] P2O5 is a component that enhances ion exchange performance, particularly increasing the stress depth. However, if the content of P2O5 is too high, the glass tends to undergo phase separation and water resistance tends to decrease. Therefore, the content of P2O5 is preferably 0 to 20%, 0.5 to 19%, 1 to 18%, and particularly preferably 2 to 15%.
[0038] The total content of Al2O3 and MgO is preferably more than 20 to 55%, 25 to 50%, 30 to 45%, 32 to 42%, and particularly preferably 35 to 40%. If the total content of Al2O3 and MgO is too small, the fracture toughness K 1C is likely to decrease.
[0039] [MgO] / [Al2O3] is preferably 0.9 or more, 1.2 or more, and particularly 1.5 to 3.5. If [MgO] / [Al2O3] is too small, the fracture toughness K 1C It becomes difficult to increase the melting property and moldability while decreasing the melting property and moldability.
[0040] [MgO] / [Na2O] is preferably 1.0 or more, 1.5 or more, and particularly 2.0 to 20. If [MgO] / [Na2O] is too small, the fracture toughness K 1C is likely to decrease.
[0041] Glass composition range B contains, in mole percent, SiO2 60-80%, Al2O3 1-30%, B2O3 0-15%, Li2O > 0.1-30%, Na2O 0-20%, K2O 0-10%, and MgO 0-20%. The reasons for limiting the content range of each component are as follows. In the explanation of the content range of each component, % indicates mole percent unless otherwise specified.
[0042] SiO2 is a component that forms a glass network. The content of SiO2 is preferably 60 to 80%, 63 to 78%, and particularly 65 to 75%. If the content of SiO2 is too low, vitrification becomes difficult, and the thermal expansion coefficient becomes too high, so that the thermal shock resistance is likely to decrease. On the other hand, if the content of SiO2 is too high, meltability and moldability tend to decrease, and the thermal expansion coefficient becomes too low, so that it is difficult to match the thermal expansion coefficient of the surrounding materials.
[0043] Al2O3 has high fracture toughness K 1C It is an ingredient that increases the fracture toughness K, and also increases the ion exchange performance, strain point, and Young's modulus. If the Al2O3 content is too low, 1CThe glass tends to be degraded, and the ion exchange performance may not be fully exhibited. Therefore, the content of Al2O3 is preferably 1% or more, 5% or more, 8% or more, 10% or more, and particularly 12% or more. On the other hand, if the content of Al2O3 is too high, the high-temperature viscosity increases, and the melting property and moldability tend to decrease. In addition, devitrification crystals tend to precipitate in the glass, making it difficult to form into a plate shape by the overflow downdraw method or the like. In particular, when an alumina-based refractory is used as the molded body refractory and the glass is formed into a plate shape by the overflow downdraw method, devitrification crystals of spinel tend to precipitate at the interface with the alumina-based refractory. Furthermore, the acid resistance also decreases, making it difficult to apply to the acid treatment process. Therefore, the content of Al2O3 is preferably 30% or less, 25% or less, and particularly 21% or less.
[0044] B2O3 is a component that reduces the high-temperature viscosity and density, stabilizes the glass, and lowers the liquidus temperature. However, if the content of B2O3 is too high, the Young's modulus is likely to decrease. Therefore, the content of B2O3 is preferably 0 to 15%, 0 to 10%, 0 to 5%, and particularly preferably 0 to 1%.
[0045] Li2O is an ion exchange component, and also a component that reduces high-temperature viscosity and improves meltability and formability, as well as fracture toughness K 1C On the other hand, if the Li2O content is too high, the devitrification resistance is likely to decrease, and the Li2O content may be eluted in the ion exchange solution during ion exchange treatment, deteriorating the ion exchange solution. Therefore, the Li2O content is preferably more than 0.1 to 30%, 0.1 to 20%, 0.1 to 18%, 3 to 15%, and particularly preferably 5 to 12%.
[0046] Na2O is an ion exchange component, which increases the compressive stress value of the compressive stress layer, and also reduces the high-temperature viscosity to increase the melting property and formability. Na2O also increases the devitrification resistance, and in particular suppresses the devitrification caused by the reaction with an alumina-based refractory. If the Na2O content is too high, it becomes difficult to obtain the above effects. On the other hand, if the Na2O content is too low, the high-temperature viscosity increases, which reduces the melting property and formability, and the compressive stress value of the compressive stress layer is likely to decrease. Therefore, the Na2O content is preferably 0 to 20%, 0 to less than 10%, and particularly 0.1 to 5%.
[0047] K2O is a component that reduces high-temperature viscosity and improves melting and moldability, but among alkali metal oxides, it is a component that reduces the compressive stress value of the compressive stress layer and increases the stress depth, so it is not advantageous from the viewpoint of increasing the compressive stress value. Therefore, the content of K2O is preferably 0 to 10%, 0 to 5%, and particularly 0 to less than 1%.
[0048] MgO has high fracture toughness. 1C It is a component that significantly increases the melting property and formability, and is a component that increases the melting property and formability. However, if the content of MgO is too high, the devitrification resistance is likely to decrease, and in particular, it becomes difficult to suppress the devitrification caused by the reaction with the alumina-based refractory. Therefore, the content of MgO is preferably 0 to 20%, more preferably 0 to 20%, 0 to 10%, 0 to 8%, 0.1 to 5%, and particularly preferably 1 to 3%.
[0049] P2O5 is a component that enhances ion exchange performance, particularly increasing the stress depth. However, if the content of P2O5 is too high, the glass tends to undergo phase separation and water resistance tends to decrease. Therefore, the content of P2O5 is preferably 0 to 10%, 0 to 3%, 0 to 1%, and particularly preferably 0 to 0.5%.
[0050] In addition to the above components, the glass composition ranges A and B may contain, for example, the following components.
[0051] Compared with other components, CaO is a component that is highly effective in reducing high-temperature viscosity and improving meltability and moldability without reducing devitrification resistance. However, if the CaO content is too high, the ion exchange performance decreases and the ion exchange solution is easily deteriorated during ion exchange treatment. Therefore, the CaO content is preferably 0 to 6%, 0 to 5%, 0 to 4%, 0 to 3.5%, 0 to 3%, 0 to 2%, 0 to 1%, and particularly 0 to 0.5%.
[0052] SrO and BaO are components that reduce high-temperature viscosity, improve meltability and formability, and increase the strain point and Young's modulus. However, if their content is too high, the fracture toughness K 1C In addition to the tendency for the glass to decrease in viscosity, the density and thermal expansion coefficient increase, and the glass is prone to devitrification. Therefore, the suitable contents of SrO and BaO are 0 to 5%, 0 to 2%, 0 to 1.5%, 0 to 1%, 0 to 0.5%, and 0 to 0.1%, particularly preferably 0 to less than 0.1%, respectively.
[0053] ZnO is a component that reduces high-temperature viscosity without reducing low-temperature viscosity. It is also a component that enhances ion exchange performance, and is particularly effective in increasing the compressive stress value. However, if the ZnO content is too high, the glass tends to undergo phase separation, the devitrification resistance to decrease, the density to increase, and the stress depth to decrease. Therefore, the ZnO content is preferably 0 to 3%, 0 to 2%, 0 to 1%, and particularly less than 0 to 1%.
[0054] ZrO2 is a component that increases the Young's modulus and also increases the viscosity near the liquidus viscosity and the strain point, but if the content is too high, there is a risk of the devitrification resistance being significantly reduced. Therefore, the content of ZrO2 is 0 to 10%, 0 to 5%, 0 to 3%, preferably 0 to 1%, and particularly 0 to 0.1%.
[0055] TiO2 is a component that increases the ion exchange performance Young's modulus and also reduces the high-temperature viscosity, but if the content is too high, the transparency and devitrification resistance tend to decrease. Therefore, the TiO2 content is preferably 0 to 10%, 0 to 4.5%, 0 to less than 1%, 0 to 0.5%, and particularly 0 to 0.3%.
[0056] SnO2 is a component that enhances ion exchange performance, but if the content is too high, the devitrification resistance is likely to decrease. Therefore, the content of SnO2 is preferably 0 to 3%, 0.01 to 3%, 0.05 to 3%, 0.1 to 3%, and particularly preferably 0.2 to 3%.
[0057] As a fining agent, one or more selected from the group consisting of Cl, SO3 and CeO2 (preferably Cl and SO3) may be added in an amount of 0.001 to 1%.
[0058] In addition, 0.001 to 1% of Sb2O3 may be added as a fining agent. An effective fining agent can be added depending on the high temperature viscosity, which varies depending on the glass composition.
[0059] The preferred content of Fe2O3 is less than 1000 ppm (less than 0.1%), less than 800 ppm, less than 600 ppm, less than 400 ppm, and particularly less than 300 ppm. Furthermore, it is preferred that the molar ratio SnO2 / (Fe2O3+SnO2) is regulated to 0.8 or more, 0.9 or more, and particularly 0.95 or more, while restricting the content of Fe2O3 to the above range. In this way, the total light transmittance at a wavelength of 400 to 770 nm and a thickness of 1 mm is easily improved.
[0060] Y2O3 has high fracture toughness. 1C However, the raw material cost of Y2O3 itself is high, and adding a large amount of Y2O3 tends to reduce devitrification resistance. Therefore, the content of Y2O3 is preferably 0 to 15%, 0.1 to 12%, 1 to 10%, 1.5 to 8%, and particularly preferably 2 to 6%.
[0061] Gd2O3, Nb2O5, La2O3, and Ta2O5 have high fracture toughness. 1C However, the raw materials for Gd2O3, Nb2O5, La2O3, and Ta2O5 are expensive, and adding a large amount of them tends to reduce devitrification resistance. The total and individual contents of Gd2O3, Nb2O5, La2O3, and Ta2O5 are preferably 0 to 15%, 0 to 10%, 0 to 5%, and particularly preferably 0 to 3%.
[0062] From an environmental perspective, the cover glass of the present invention preferably does not substantially contain As2O3, PbO, F, etc. as a glass composition. Also, from an environmental perspective, it is also preferable that the cover glass does not substantially contain Bi2O3. The phrase "substantially does not contain ..." means that the specified components are not actively added as glass components, but impurity-level addition is permitted, and specifically refers to the case where the content of the specified components is less than 0.05%.
[0063] In addition to the above properties, the cover glass of the present invention preferably has the following properties.
[0064] The density is preferably 3.50 g / cm 3 Below, 3.25g / cm 3 Below 3.00g / cm 3 Below, 2.90g / cm 3 Below 2.80g / cm 3 Below 2.70g / cm 3 Below, 2.60g / cm 3 Below 2.55g / cm 3 Below 2.50g / cm 3 Below, 2.49g / cm 3 The following, especially 2.40 to 2.47 g / cm 3 The lower the density, the lighter the cover glass can be. Note that the density can be easily reduced by increasing the content of SiO2, B2O3, and P2O5 in the glass composition, or by decreasing the content of alkali metal oxides, alkaline earth metal oxides, ZnO, ZrO2, and TiO2.
[0065] High temperature viscosity 10 2.5 The temperature at dPa·s is preferably 1660° C. or less, less than 1640° C., 1630° C. or less, 1620° C. or less, and although there is no particular lower limit, 1600° C. to 1400° C. is preferred. 2.5 If the temperature at dPa·s is too high, the melting property and formability decrease, making it difficult to form the molten glass into a sheet.
[0066] The liquidus viscosity is preferably 10 3.0dPa s or more, 10 3.5 dPa s or more, 10 4.0 dPa s or more, 10 4.4 dPa s or more, 10 4.8 dPa s or more, 10 5.0 dPa s or more, 10 5.3 dPa s or more, especially 10 5.5 It is dPa·s or more. The higher the liquidus viscosity, the better the resistance to devitrification and the less likely devitrification particles will occur during molding. Here, "liquidus viscosity" refers to the value of the viscosity at the liquidus temperature measured using the platinum ball pull-up method. "Liquidus temperature" is the highest temperature at which devitrification (devitrification particles) is observed inside the glass when glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains on the 50 mesh (300 μm) is placed in a platinum boat and held in a temperature gradient furnace for 24 hours, after which the platinum boat is removed and observed under a microscope.
[0067] In the cover glass of the present invention, the plate thickness is preferably 2.0 mm or less, 1.5 mm or less, 1.3 mm or less, 1.1 mm or less, 1.0 mm or less, particularly 0.9 mm or less. The smaller the plate thickness, the lighter the cover glass can be. On the other hand, if the plate thickness is too thin, it is difficult to obtain the desired mechanical strength. Therefore, the plate thickness is preferably 0.3 mm or more, 0.4 mm or more, 0.5 mm or more, 0.6 mm or more, particularly 0.7 mm or more.
[0068] The method for producing the cover glass of the present invention is, for example, as follows. First, glass raw materials prepared to obtain a desired glass composition are charged into a continuous melting furnace, heated and melted at 1400 to 1700°C, and then clarified. The molten glass is then fed to a molding device, formed into a plate, and cooled. After forming into a plate, a known method can be used to cut the glass into a predetermined size.
[0069] As a method for forming molten glass into a plate shape, it is preferable to adopt the overflow down-draw method. The overflow down-draw method is a method capable of mass-producing high-quality cover glass. Here, the "overflow down-draw method" is a method in which molten glass is made to overflow from both sides of a molded refractory body, and the overflowed molten glass is drawn downward while being joined at the lower end of the molded refractory body to form a plate shape. In the overflow down-draw method, the surface to be the surface of the cover glass does not contact the surface of the molded refractory body, and is formed into a plate shape in a free surface state. Therefore, unpolished cover glass with good surface quality can be produced at low cost.
[0070] In addition to the overflow downdraw method, various other forming methods can be used, such as the float method, the downdraw method (slot downdraw method, redraw method, etc.), the roll-out method, and the press method.
[0071] The cover glass of the present invention may be subjected to ion exchange treatment or not. However, when the cover glass is subjected to ion exchange treatment, a compressive stress layer is formed on the surface, so that the fracture toughness K 1C The condition of the ion exchange treatment is not particularly limited, and the optimum condition may be selected in consideration of the viscosity characteristics, thickness, internal tensile stress, dimensional change, etc. of the glass. In particular, when K ions in the KNO3 molten salt are ion-exchanged with the Na component in the glass, the compressive stress layer can be efficiently formed. In the ion exchange treatment, the temperature of the ion exchange solution is preferably 400 to 450°C, and the ion exchange time is preferably 2 to 6 hours. In this way, the compressive stress layer can be efficiently formed on the surface. In addition, Na ions in the NaNO3 molten salt and the mixed molten salt of KNO3 and NaNO3 may be ion-exchanged with the Li component in the glass.
[0072] The cover glass of the present invention preferably has a compressive stress layer formed by ion exchange on the surface, and the compressive stress layer preferably has a compressive stress value of 300 MPa or more, 400 MPa or more, 500 MPa or more, 600 MPa or more, and particularly preferably 700 MPa or more. 1COn the other hand, if an extremely large compressive stress is formed on the surface, the inherent tensile stress becomes extremely high, and there is a risk of a large change in dimensions before and after the ion exchange treatment. For this reason, the compressive stress value of the compressive stress layer is preferably 1800 MPa or less, 1650 MPa or less, and particularly preferably 1500 MPa or less. In addition, if the ion exchange time is shortened or the temperature of the ion exchange solution is lowered, the compressive stress value tends to increase.
[0073] The stress depth of the compressive stress layer is preferably 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, and particularly 35 μm or more. The greater the stress depth, the smaller the variation in mechanical strength. On the other hand, the greater the stress depth, the higher the inherent tensile stress becomes, and there is a risk of a large dimensional change before and after the ion exchange treatment. Furthermore, if the stress depth is too large, the compressive stress value tends to decrease. Therefore, the stress depth is preferably 60 μm or less, 50 μm or less, and particularly 45 μm or less. In addition, if the ion exchange time is extended or the temperature of the ion exchange solution is increased, the stress depth tends to increase.
[0074] The internal tensile stress value is preferably 150 MPa or less, 120 PMa or less, 100 MPa or less, 80 MPa or less, 70 MPa or less, particularly 60 MPa or less. If the internal tensile stress value is too high, the cover glass is likely to self-destruct due to hard scratches. On the other hand, if the internal tensile stress value is too low, it is difficult to ensure the mechanical strength of the cover glass. The internal tensile stress value is preferably 15 MPa or more, 25 MPa or more, 35 MPa or more, particularly 40 MPa or more. The internal tensile stress value is a value calculated by (compressive stress value x stress depth) / (plate thickness - 2 x stress depth), and can be measured by the software FsmV of the surface stress meter FSM-6000LE of Orihara Seisakusho.
[0075] The CT limit is preferably 65 MPa or more, 70 MPa or more, 80 MPa or more, or 90 MPa or more, particularly 100 MPa to 300 MPa. The CT limit converted into a plate thickness of 0.5 mm is preferably 65 MPa or more, 70 MPa or more, 80 MPa or more, or 90 MPa or more, particularly 100 MPa to 300 MPa. If the CT limit is too low, it becomes difficult to increase the stress depth, and it becomes difficult to ensure the mechanical strength of the cover glass.
[0076] The cover glass of the present invention is preferably an amorphous glass, but may be crystallized by heat treatment or the like to become a crystallized glass. EXAMPLES
[0077] The present invention will be described below based on examples. Note that the following examples are merely illustrative and the present invention is not limited to the following examples.
[0078] Table 1 shows the glass compositions and glass properties of the examples of the present invention (samples Nos. 1 to 14).
[0079] [Table 1]
[0080] Each sample in the table was prepared as follows. First, glass raw materials were mixed to obtain the glass composition in the table, and melted at 1550°C for 21 hours using a platinum pot. The resulting molten glass was then poured onto a carbon plate, formed into a flat plate shape, and slowly cooled in a slow cooling furnace. The surface of the resulting plate glass was optically polished to a plate thickness of 0.8 mm, and various properties were evaluated.
[0081] The Young's modulus E is a value measured by the well-known resonance method.
[0082] Fracture toughness K 1Cwas measured using the SEPB method based on JIS R1607 "Fracture toughness test method for fine ceramics." The fracture toughness value of each glass was calculated as the average value of five points.
[0083] As is clear from Table 1, samples No. 1 to No. 14 had fracture toughness K 1C Since the value is 0.9 or more, it is considered to have high scratch resistance. EXAMPLES
[0084] Table 2 shows the glass compositions and glass properties of an example of the present invention (sample No. 15) and a comparative example (sample No. 16).
[0085] [Table 2]
[0086] Each sample in the table was prepared as follows. First, glass raw materials were mixed to obtain the glass composition in the table, and melted at 1450°C for 8 hours using a platinum pot. The resulting molten glass was then poured onto a carbon plate, formed into a flat plate shape, and slowly cooled in a slow cooling furnace. The surfaces of the resulting plate glasses were optically polished to obtain various plate thicknesses, and various properties were evaluated.
[0087] Young's modulus E and fracture toughness K 1C was determined by the above method.
[0088] The density is a value measured by the well-known Archimedes method.
[0089] The thermal expansion coefficient α is a value measured in the temperature range of 30 to 380°C using a dilatometer.
[0090] The photoelastic constant is a value calculated using a photoelastic constant measuring device manufactured by Uniopto.
[0091] The refractive index nd was measured by the V-block method. nd is the refractive index at the d line.
[0092] Next, for samples No. 15 and 16, each sample was immersed in KNO3 molten salt at 430 to 480°C for 4 to 8 hours to perform ion exchange treatment, and tempered glass having various CTcv values was obtained for each plate thickness. The CTcv values were obtained from the CTcv values of the soft FsmV of the surface stress meter FSM-6000LE manufactured by Orihara Seisakusho, based on the above-mentioned photoelastic constant and refractive index nd.
[0093] Next, ion exchange treatment was carried out under various conditions for samples No. 15 and No. 16 of various plate thicknesses to produce tempered glass with different stress states. Next, an indenter test was carried out using a diamond tip on a surface plate, and the number of fragments with dimensions of 0.1 mm or more when delayed fracture occurred was 100 pieces / inch. 2 The number of fragments at CTcv values (2 points) exceeding 100 fragments / inch 2 Data on the number of fragments at CTcv values (2 points) when the number of fragments was less than 100 was also collected. The data on the number of fragments at each point was the average of three measurements. Furthermore, an exponential approximation curve was drawn from the data on the number of fragments at a total of four CTcv values, and the CTcv value at which the number of fragments becomes 100 was calculated from the approximation curve as the CT limit. The results are shown in Figure 3. In Figure 3, the dotted line is a graph showing the relationship between the plate thickness and the CT limit for sample No. 15, and the solid line is a graph showing the relationship between the plate thickness and the CT limit for sample No. 16.
[0094] As can be seen from FIG. 3, sample No. 15 had a fracture toughness of K 1C Therefore, the CT limit was higher than that of sample No. 16.
Claims
1. SiO in the glass composition 2 The content of Al is 30 to 70 mol %. 2 O 3 The content of is 10 to 25 mol %, 2 O 5 The content is 1 mol% or more, and the fracture toughness K 1C is 0.9MPa・m 0.5 A cover glass characterized by the above.
2. 2. The cover glass of claim 1, wherein the glass composition contains more than 10 mol % MgO.
3. The glass composition is, in mol%, SiO 2 30-70%, Al 2 O 3 10-25%, B 2 O 3 0-15%, Li 2 O 0-7%, Na 2 O 0-20%, K 2 3. The cover glass according to claim 1, comprising 0 to 10% O and more than 10 to 50% MgO.
4. P in the glass composition 2 O 5 4. The cover glass according to claim 1, wherein the content of is 2 mol % or more.
5. [MgO] / [Al 2 O 3 5. The cover glass according to claim 1, which satisfies the relationship: .gtoreq.0.
9.
6. [MgO] / [Na 2 6. The cover glass according to claim 1, wherein the relationship: [0.01]≧1.0 is satisfied.
7. Li in the glass composition 2 2. The cover glass of claim 1, wherein the O content is greater than 0.1 mol %.
8. Y in the glass composition 2 O 3 8. The cover glass according to claim 1, further comprising 0.1 mol % or more of
9. 9. The cover glass according to claim 1, wherein the cover glass has a Young's modulus of 90 GPa or more.
10. 10. The cover glass according to claim 1, further comprising a compressive stress layer formed on the surface thereof by ion exchange.
11. 11. The cover glass according to claim 10, wherein the compressive stress layer has a compressive stress value of 300 MPa or more and a stress depth of 15 μm or more.
12. 12. The cover glass according to claim 10, wherein the CT limit calculated based on a plate thickness of 0.5 mm is greater than 65 MPa.
13. The cover glass according to any one of claims 1 to 12, which is used for a touch panel display.
Citation Information
Patent Citations
Plate glass and electronic substrate glass
JP2000103638A
Glass for information recording medium substrate
JP2000159540A
Glass composition and glass substrate
JP2004277232A
Glass composition, glass substrate for information recording medium using it and information recording medium
JP2005272212A
Glass member
JP2006083045A